Lorcaserin improves glycemic control via a melanocortin neurocircuit - Burke, Luke K. (2017)
Objective: The increasing prevalence of type 2 diabetes (T2D) and associated morbidity and mortality emphasizes the need for a more complete understanding of the mechanisms mediating glucose homeostasis to accelerate the identification of new medications. Recent reports indicate that the obesity medication lorcaserin, a 5-hydroxytryptamine (5-HT, serotonin) 2C receptor (5-HT2CR) agonist, improves glycemic control in association with weight loss in obese patients with T2D. Here we evaluate whether lorcaserin has an effect on glycemia without body weight loss and how this effect is achieved. Methods: Murine models of common and genetic T2D were utilized to probe the direct effect of lorcaserin on glycemic control. Results: Lorcaserin dose-dependently improves glycemic control in mouse models of T2D in the absence of reductions in food intake or body weight. Examining the mechanism of this effect, we reveal a necessary and sufficient neurochemical mediator of lorcaserin's glucoregulatory effects, brain pro-opiomelanocortin (POMC) peptides. To clarify further lorcaserin's therapeutic brain circuit, we examined the receptor target of POMC peptides. We demonstrate that lorcaserin requires functional melanocortin4 receptors on cholinergic preganglionic neurons (MC4RChAT) to exert its effects on glucose homeostasis. In contrast, MC4RChAT signaling did not impact lorcaserin's effects on feeding, indicating a divergence in the neurocircuitry underpinning lorcaserin's therapeutic glycemic and anorectic effects. Hyperinsulinemic-euglycemic clamp studies reveal that lorcaserin reduces hepatic glucose production, increases glucose disposal and improves insulin sensitivity. Conclusions: These data suggest that lorcaserin's action within the brain represents a mechanistically novel treatment for T2D: findings of significance to a prevalent global disease.